Low viscosity high strength spherical silica for 3D printing photosensitive resin

CN122958770APending Publication Date: 2026-10-23JIAN YUSHUN NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611086886.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-21
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0003]现阶段球形二氧化硅高比例填充光敏树脂仍存在诸多技术难题:高填充工况下填料易团聚,大幅提升树脂浆料黏度,破坏打印流平与铺展性能;填料与树脂界面结合薄弱,易产生应力集中、诱发裂纹扩展,造成制品力学性能衰减;同时填料分散稳定性差,长期储存易沉降分层,降低树脂储存稳定性与打印工艺重复性

Benefits of technology

[0027]本发明所述的低粘高强球形二氧化硅及其在3D打印光敏树脂中的应用,相比现有技术具有以下有益效果:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122958770A_ABST
    Figure CN122958770A_ABST
Patent Text Reader

Abstract

The application discloses a kind of low viscosity high-strength spherical silica for 3D printing photosensitive resin, belong to functional material technical field, the spherical silica is treated with multiple anchoring hybrid functional copolymer on surface, the copolymer includes urea-based phosphate methacrylate, trisiloxane methacrylate, sulfonyl fluoride styrene, vinyl trimethoxysilane and other functional monomers, by hydrogen bond adsorption, chemical bonding and other multiple anchoring mechanisms form dense stable organic coating on the surface of silicon dioxide.The modified spherical silica is filled into acrylate photosensitive resin at high proportion, and 3D printing photosensitive resin material with low viscosity, high stability and high mechanical properties can be obtained.The resin is superior to traditional filler modification system in the bending strength and tensile strength of the product after photocuring molding, and is suitable for precision 3D printing manufacturing field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of non-metallic additive materials technology, specifically relating to a low-viscosity, high-strength spherical silica for use in 3D printing photosensitive resins. Background Technology

[0002] Photopolymer 3D printing is an additive manufacturing technology that relies on the layer-by-layer curing of photosensitive resin to form 3D products. With its advantages of high forming precision, excellent surface quality, and fast forming speed, it is widely used in precision casting, dental medicine, jewelry design, and electronics. The performance of the photosensitive resin directly determines the forming effect and performance of the 3D printed products. To improve the mechanical properties and dimensional stability of printed products, the industry often uses spherical silica as an inorganic reinforcing filler. This material has advantages such as regular morphology, controllable particle size, and good chemical stability, making it an ideal reinforcing filler for photosensitive resins. However, the surface of unmodified spherical silica is rich in hydrophilic silanol groups, which have extremely poor compatibility with hydrophobic acrylate resin matrices, severely limiting the application effect of composite resins.

[0003] At present, there are still many technical challenges in using high-proportion spherical silica-filled photosensitive resins: under high-filling conditions, the filler is prone to agglomeration, which greatly increases the viscosity of the resin slurry and damages the printing leveling and spreading performance; the interface between the filler and the resin is weak, which easily leads to stress concentration, induces crack propagation, and causes the mechanical properties of the product to deteriorate; at the same time, the filler has poor dispersion stability and is prone to sedimentation and stratification during long-term storage, which reduces the storage stability of the resin and the repeatability of the printing process.

[0004] Traditional silane coupling agent modification can only slightly improve interfacial compatibility, and suffers from defects such as thin coating layer, poor uniformity, and insufficient stability. Furthermore, it cannot chemically bond with photosensitive resins, resulting in limited interfacial reinforcement. Emerging polymer brush grafting modification technology can optimize filler dispersion, but existing modifiers have limited functionality and cannot simultaneously meet the multiple requirements of strong filler anchoring, resin compatibility, and photocuring reaction. Therefore, developing novel silica surface modifiers with multiple anchoring mechanisms and multifunctional chain segments is key to achieving low-viscosity, high-strength filling of photosensitive resins, and has significant engineering application value. Summary of the Invention

[0005] To overcome the shortcomings of the prior art, this invention provides a low-viscosity, high-strength spherical silica for 3D printing photosensitive resins. The technical solution to achieve the objective of this invention is as follows: A low-viscosity, high-strength spherical silica comprises spherical silica and a multi-anchoring hybrid functional copolymer coated on its surface. By weight, it comprises 100 parts of spherical silica and 3-5 parts of the multi-anchoring hybrid functional copolymer. The multi-anchoring hybrid functional copolymer is prepared by reacting the following monomers by weight: 35-50 parts of urea-phosphate methacrylate monomer, 12-22 parts of trisiloxane methacrylate monomer, 3-8 parts of sulfonyl fluorostyrene monomer, 4-10 parts of vinyltrimethoxysilane, 19-38 parts of acrylate modifier monomer, and 0.5-2 parts of dimethacrylate. The structure of the urea-phosphate methacrylate monomer is shown in Formula 1; the structure of the trisiloxane methacrylate monomer is shown in Formula 2; and the structure of the sulfonyl fluorostyrene monomer is shown in Formula 3. Formula 1, wherein R is selected from C8~C18 straight-chain, branched alkyl chain or benzyl; Equation 2; Equation 3, where R' is -CH2SO2F, and the substitution position is either anti- or meta-position.

[0006] The amount of ethylene glycol dimethacrylate is controlled at 0.5 to 2 parts. Under the reaction conditions of 20% to 30% solid content, it mainly forms a slightly branched structure, with intramolecular cyclization and intermolecular crosslinking competing and coexisting. The product is still soluble in tetrahydrofuran and anhydrous ethanol. According to GPC, its apparent number-average molecular weight is 8000 to 15000, and its molecular weight distribution index (PDI) is 1.5 to 2.5. The particle size of the spherical silica is 1 to 50 μm. The acrylate regulating monomers are selected from one or more of methyl methacrylate, butyl acrylate, and isobornyl methacrylate.

[0007] The preparation method of the multi-anchoring hybrid functional copolymer includes the following steps: Urea phosphate methacrylate monomer, trisiloxane methacrylate monomer, sulfonyl fluorostyrene monomer, vinyltrimethoxysilane, acrylate modifier monomer and ethylene glycol dimethacrylate are dissolved in a mixed solvent, and an initiator is added to form a reaction solution. The reaction solution is heated to 70-80°C under nitrogen protection to carry out the polymerization reaction. After the reaction is completed, the reaction solution is cooled to room temperature, poured into a precipitant to precipitate, and after washing and drying, a multi-anchored hybrid functional copolymer is obtained.

[0008] Specifically, the mixed solvent is a mixture of butanone and toluene in a volume ratio of (0.5~2):1, with the total solid content controlled at 20%~30%; the initiator is azobisisobutyronitrile, and the amount used is 0.5%~2% of the total weight of the monomers; the precipitant is selected from one or two of n-hexane and petroleum ether.

[0009] The method for preparing the ureophosphate methacrylate monomer includes the following steps: The phosphorylating agent was dissolved in dry dichloromethane and cooled to a low temperature. A long-chain alcohol and an acid-binding agent were dissolved in dry dichloromethane and gently heated to aid dissolution, then cooled for later use. The mixture of the long-chain alcohol and the acid-binding agent was slowly added dropwise at a low temperature. After the reaction at low temperature, the temperature was slowly increased, then raised to room temperature with stirring. The mixture was filtered under an inert atmosphere to remove the salt, and the filter cake was washed with dry dichloromethane. The combined filtrates were concentrated under reduced pressure under an inert atmosphere to obtain alkylphosphoryl dichloride, which was immediately used in the next step. A protected amino alcohol was dissolved in dry dichloromethane, and an acid-binding agent was added. The mixture was cooled to a low temperature, and the above-mentioned alkylphosphoryl dichloride solution in dry dichloromethane was added dropwise. The reaction was stirred at a low temperature. After the reaction was complete, the mixture was filtered under an inert atmosphere to remove the salt. The filtrate was concentrated under reduced pressure under an inert atmosphere to obtain a chlorophosphate intermediate. The intermediate was dissolved in a mixture of organic solvent and water, and an alkaline solution was added to hydrolyze the phosphoryl chloride bonds. The organic solvent was removed by concentration under reduced pressure. The residual aqueous phase was acidified with dilute acid, and then extracted with an organic solvent, salted out, and demulsified. The combined organic phases were dried, concentrated under reduced pressure, and dissolved in dichloromethane. After cooling to low temperature, a mixture of deprotecting reagents was added to remove the protecting group. The reaction was carried out at room temperature, and the deprotecting reagents were removed by concentration under reduced pressure. The mixture was dissolved in a mixed solvent and then concentrated under reduced pressure to completely remove the residual deprotecting reagents. The residue was dissolved in the mixed solvent, and an acid-binding agent was added. The mixture was sonicated under an inert atmosphere to completely dissociate and dissolve the amine salt. The mixture was cooled to low temperature, and isocyanate methacrylate was added dropwise. The mixture was stirred at low temperature and then heated to room temperature. Alcohol was added and stirred at room temperature to quench the residual isocyanate. The residual alcohol was removed by concentration under reduced pressure. The residue was dissolved in dichloromethane and washed with dilute acid to remove the acid-binding agent. The mixture was first washed with deionized water and then with saturated sodium chloride to demulsify and remove residual water and inorganic salts. The organic phase was dried, concentrated under reduced pressure, and purified by column chromatography. After the reaction was completed, a polymerization inhibitor was added to the feed solution and maintained throughout the process. The purified product was stored in a solution containing the polymerization inhibitor at low temperature and protected from light to obtain the ureophosphate methacrylate monomer.

[0010] The long-chain alcohol is selected from C8-C18 straight-chain or branched alkyl alcohols or aromatic alcohols, and further selected from dodecyl alcohol or benzyl alcohol; the protected amino alcohol is selected from tert-butoxycarbonyl-protected 2-amino-3-phenylprop-1-ol; the acid-binding agent is selected from triethylamine; the phosphorylation reagent is selected from phosphorus oxychloride; the alkaline solution is selected from 0.5-1.0 M sodium hydroxide aqueous solution; the dilute acid is selected from 0.1-0.5 M dilute hydrochloric acid; the deprotection reagent is selected from trifluoroacetic acid; the alcohol is selected from methanol; the polymerization inhibitor is selected from 0.1 wt% hydroquinone monomethyl ether; the organic solvent is selected from one or more of tetrahydrofuran, ethyl acetate, dimethylformamide, anhydrous ethanol or dichloromethane; the column chromatography purification uses a neutral alumina column, and the eluent is selected from a mixed solvent of dichloromethane and methanol in a volume ratio of (8-10):1 and contains 0.5%-1% triethylamine.

[0011] The preparation method of the trisiloxane methacrylate monomer includes the following steps: Under an inert atmosphere, allyl methacrylate was mixed with a polymerization inhibitor and a hydrosilylation catalyst. After heating, hydrogen-containing dichlorosilane was slowly added dropwise. When half of the mixture was added, the hydrosilylation catalyst was added to continue the reaction, utilizing the exothermic reaction to obtain a hydrosilylation intermediate. The above hydrosilylation intermediate was dissolved in an ether solvent, an acid-binding agent was added, and the mixture was pre-cooled at a low temperature. Then, sodium trimethylsilanolate was slowly added dropwise. After the addition was complete, the mixture was stirred continuously, filtered to remove the salt, and the filtrate was concentrated under reduced pressure to remove the solvent and residual volatile impurities, yielding the trisiloxane methacrylate monomer.

[0012] The hydrogen-containing dichlorosilane is selected from methyldichlorosilane; the polymerization inhibitor is selected from 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxy radical; the hydrosilylation catalyst is selected from platinum catalyst; the acid-binding agent is selected from pyridine; and the ether solvent is selected from diethyl ether.

[0013] Since the steric hindrance of the allyl double bond is less than that of the methacrylate double bond, under the conditions of low-temperature drop addition and platinum catalysis, the hydrosilylation selectively occurs at the allyl position, and the methacrylate double bond retention rate is greater than 90%. Subsequent 1H NMR spectroscopy confirmed that the main addition product is the allyl addition.

[0014] The preparation method of the sulfonyl fluorostyrene monomer includes the following steps: Starting with halomethylstyrene, the first step involves a nucleophilic substitution reaction between halomethylstyrene and sulfite in an alcohol-water mixture. A polymerization inhibitor is added to the reaction system, and the reaction is refluxed under an inert atmosphere. After the reaction is complete, the mixture is cooled to room temperature, filtered to remove the precipitate, and the filtrate is concentrated to dryness under reduced pressure. The filtrate is then recrystallized from anhydrous alcohol and dried under vacuum to obtain vinylbenzylsulfonate. The vinylbenzylsulfonate is then dried under vacuum to remove water, mixed with phosphorus pentahalide in dry toluene, and a polymerization inhibitor is added. The mixture is stirred from a low temperature and slowly heated to no more than 50°C. After the reaction is complete, the mixture is cooled to room temperature and quenched in ice water with vigorous stirring. The organic phase is separated, dried, concentrated under reduced pressure, and purified by column chromatography to obtain vinylbenzylsulfonyl halide. The vinylbenzylsulfonyl halide is then mixed with anhydrous fluorinating agent in dry acetonitrile, and a phase transfer catalyst and polymerization inhibitor are added. The mixture is refluxed under an inert atmosphere, and the endpoint is monitored by thin-layer chromatography. After the reaction is complete, the mixture is cooled to room temperature, filtered to remove the precipitate, and the filtrate is concentrated under reduced pressure and purified by column chromatography to obtain sulfonyl fluorostyrene monomer.

[0015] The halomethylstyrene is selected from 4-chloromethylstyrene or 1-(chloromethyl)-3-vinylbenzene; the sulfite is selected from anhydrous sodium sulfite; the phosphorus pentahalide is selected from phosphorus pentachloride, and the dosage is 1.05~1.2 eq; the anhydrous fluorinating agent is selected from anhydrous potassium fluoride; the phase transfer catalyst is selected from 18-crown ether-6; the polymerization inhibitor is selected from hydroquinone monomethyl ether; the alcohol-water mixed solvent is selected from a mixed solvent with a volume ratio of ethanol to water of (3~5):1; the anhydrous alcohol is selected from anhydrous ethanol.

[0016] A method for preparing low-viscosity, high-strength spherical silica includes the following steps: The multi-anchoring hybrid copolymer was dissolved in anhydrous ethanol, and spherical silica was added to the solution and ultrasonically dispersed. A mixture of dilute acetic acid and deionized water at a volume ratio of 0.5~2:1 was added dropwise to adjust the pH of the system to 5.5~7.0. The mixture was stirred at room temperature to allow the silanoxy groups in the copolymer to undergo a condensation reaction with the surface of the silica. After the reaction was completed, the mixture was filtered, washed, and vacuum dried to obtain low-viscosity, high-strength spherical silica.

[0017] The dilute acetic acid is a 0.1~0.5 M aqueous acetic acid solution; the vacuum drying temperature is 35~45℃; when adjusting the pH of the system, dilute ammonia water is added if necessary to adjust it to 5.5~7.0.

[0018] A 3D printing photosensitive resin, by weight, comprises 30-50 parts of the aforementioned low-viscosity high-strength spherical silica or the low-viscosity high-strength spherical silica prepared by the aforementioned method, 35-55 parts of acrylate resin matrix, 5-12 parts of reactive diluent, 1.2-2.5 parts of photoinitiator system, and 0.01-0.05 parts of polymerization inhibitor.

[0019] Specifically, the acrylate resin matrix is ​​a mixture of bisphenol A ethoxylated diacrylate and trimethylolpropane triacrylate in a mass ratio of (5~8):(2~5); the reactive diluent is 1,6-hexanediol diacrylate; the photoinitiator system is composed of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, isopropylthioxanthone, and a hydrogen donor in a mass ratio of (2~4):1:(0.5~1.0); the hydrogen donor is selected from ethyl dimethylaminobenzoate, methyl diethanolamine, or isooctyl dimethylaminobenzoate.

[0020] A method for preparing a 3D printing photosensitive resin includes the following steps: S1. Mix the acrylate resin matrix, reactive diluent, photoinitiator, hydrogen donor and polymerization inhibitor under light-protected conditions, heat and stir until completely dissolved to obtain resin premix; S2. Add the low-viscosity, high-strength spherical silica to the resin premix in 2 to 4 portions, and disperse it for 20 to 40 minutes at 1500 to 2500 rpm using a planetary high-speed disperser. S3. Vacuum degassing for 20~40 min to obtain a uniform photosensitive resin slurry.

[0021] Another objective of this invention is to protect the application of the 3D printing photosensitive resin described above in photopolymerization 3D printing, using a DLP type 3D printing device with a wavelength of 405 nm for printing, with a single-layer exposure time of 1.5~3 s and a layer thickness of 50~150 μm. After printing, the resin is first irradiated with a 405 nm light source for 10 min for post-curing, and then heat-treated in an oven at 60°C for 30 min.

[0022] This invention uses a multi-anchoring hybrid functional copolymer surface treatment agent to coat and modify spherical silica, which can construct an organic coating layer on the filler surface that combines multiple anchoring mechanisms and polymer brush structure, thereby achieving high compatibility and high-strength interfacial bonding between silica filler and photosensitive resin matrix.

[0023] The copolymer contains three main functional anchoring units: ureophosphate methacrylate units can form multi-point hydrogen bonds and coordination with silanol groups on the silica surface through multi-point hydrogen bond adsorption, thus forming a stable physical anchor on the silica surface; trisiloxane methacrylate units can construct a hydrophobic layer on the filler surface, reducing interfacial tension and improving the dispersion stability of the filler and the flexibility of the coating layer by relying on the steric hindrance effect; sulfonyl fluoride styrene units introduce strongly polar sulfonyl fluoride side chains into the copolymer coating layer, and form a physical anchor during photocuring through strong dipole-dipole interactions and secondary hydrogen bonds with silanol groups on the filler surface, thereby enhancing the interfacial bonding force.

[0024] Simultaneously, the copolymer incorporates vinyltrimethoxysilane comonomers, which can form Si-O-Si covalent bonds through hydrolytic condensation, providing additional anchoring sites. The side-chain silaneoxy groups can further condense to form a crosslinked network, enhancing the stability of the coating layer. Acrylic esters are used to regulate the copolymer's flexibility, glass transition temperature, and matrix compatibility. Ethylene glycol dimethacrylate crosslinking agents are added to improve the structural stability and solvent resistance of the coating layer through mild branching and intramolecular cyclization.

[0025] Under weakly acidic surface treatment conditions, the trimethoxysilyl groups in the copolymer undergo controlled hydrolytic condensation, forming Si-O-Si covalent bonds with the silica surface. Simultaneously, the sulfonyl fluoride groups remain stable under these conditions, unaffected by hydrolysis. Furthermore, they exhibit low reactivity with tertiary amine hydrogen donors commonly used in photosensitive resin formulations under room temperature and light-protected storage conditions, with no significant side reactions occurring during a 90-day storage period. Through the synergistic effect of multiple mechanisms, a uniform, dense, stable, and non-detachable organic coating layer can be formed on the modified silica surface, effectively improving the wettability and dispersibility of the filler. Efficient interfacial stress transfer can be achieved during photocuring, ultimately resulting in a low-viscosity, high-strength filling effect for the photosensitive resin system.

[0026] Beneficial effects

[0027] The low-viscosity, high-strength spherical silica described in this invention and its application in 3D printing photosensitive resins have the following advantages compared to existing technologies: First, the multi-anchoring hybrid functional copolymer surface treatment agent used in this invention has multiple anchoring mechanisms, which can simultaneously form a firm bond with the spherical silica surface and the photosensitive resin matrix through multiple methods such as hydrogen bond adsorption, coordination, siloxane condensation and chemical bonding. The coating layer is dense, uniform and highly stable, thus improving the surface treatment effect.

[0028] Secondly, the modified spherical silica described in this invention exhibits excellent dispersibility and compatibility in photosensitive resins, and can maintain low slurry viscosity under high filling amounts, which is beneficial for leveling and spreading during the printing process, and improves the operability and molding accuracy of the printing process.

[0029] Third, the photosensitive resin slurry described in this invention remained uniform during a 90-day room temperature storage observation period, without significant sedimentation, which helps ensure the process repeatability of the resin material.

[0030] Fourth, the reactive groups on the surface of the modified spherical silica described in this invention, such as methacryloyl groups and sulfonyl fluoride groups, can form chemical bonds and physical anchors with the resin matrix during the photocuring process, thereby constructing a strong filler-resin interface and improving the mechanical properties of the cured product, including flexural strength and tensile strength.

[0031] Fifth, the photosensitive resin described in this invention has a suitable curing depth, enabling rapid curing and molding on conventional 3D printing equipment, resulting in high printing efficiency and good dimensional accuracy of the products.

[0032] Sixth, the preparation method provided by this invention is simple, the raw materials are readily available, the reaction conditions are mild, and it is easy to achieve large-scale production, thus having broad prospects for industrial application. Attached Figure Description

[0033] Figure 1The synthetic route for ureophosphate methacrylate monomer 1 is shown.

[0034] Figure 2 The 1H NMR spectrum is for ureophosphate methacrylate monomer 1. Detailed Implementation

[0035] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0036] Unless otherwise specified, the experimental methods used in the embodiments are conventional methods, and the materials and reagents used are commercially available unless otherwise specified.

[0037] The raw materials used in the examples and comparative examples are described below, where eq represents equivalent: Spherical silica: Spherical silica powder with a particle size of 5~20 μm is selected from Ji'an Yushun.

[0038] Platinum catalyst: Commercially available Karstedt catalyst, diluted with dry toluene to a mother liquor with a platinum content of about 100 ppm before use, and then added to the reaction system according to the calculated amount, so that the platinum atom concentration in the reaction solution is 4.5 ppm based on allyl methacrylate.

[0039] Acrylic resin matrix: A mixture of bisphenol A ethoxylated diacrylate and trimethylolpropane triacrylate in a mass ratio of 7:3, wherein the EO of bisphenol A ethoxylated diacrylate is 2 and the molecular weight is 512. Both bisphenol A ethoxylated diacrylate and trimethylolpropane triacrylate are commercially available.

[0040] Reactive diluent: 1,6-hexanediol diacrylate, commercially available.

[0041] Hydrogen donor: Ethyl dimethylaminobenzoate, commercially available.

[0042] Dilute acetic acid: 0.5M concentration, commercially available.

[0043] Urea phosphate methacrylate monomer 1 2-((2-(methacryloyloxy)ethyl)ureo)-3-phenylpropyl dodecyl phosphate: prepared in-house, the preparation method is as follows: Dissolve 1 eq of phosphorus oxychloride in dry dichloromethane and cool to -40°C. Dissolve 1.0 eq of dodecanol and 1.2 eq of triethylamine in an appropriate amount of dry dichloromethane and gently heat to 35°C to aid dissolution, then cool to 0°C for later use. Slowly add the above mixture of dodecanol and triethylamine dropwise at -40°C, react at -40°C for 1 h, then slowly raise the temperature to 0°C and stir for 1 h, then raise the temperature to room temperature and stir for 2 h. Filter through a sintered glass funnel under nitrogen protection to remove triethylamine hydrochloride, and wash the filter cake with dry dichloromethane. Combine the filtrates and concentrate under reduced pressure below 40°C under nitrogen protection to obtain dodecylphosphoryl dichloride, which is immediately used in the next step. Dissolve 1.0 eq of tert-butoxycarbonyl-protected 2-amino-3-phenylprop-1-ol in dry dichloromethane, add 1.2 eq of triethylamine, cool to 0°C, and dropwise add 1 eq of the above dodecylphosphoryl dichloride solution in dry dichloromethane. Stir at 0°C for 2 h. After the reaction was complete, the triethylamine hydrochloride was removed by filtration through a sintered glass funnel under nitrogen protection. The filtrate was concentrated under reduced pressure below 40°C under nitrogen protection to obtain a chlorophosphate intermediate. The intermediate was dissolved in a 1:1 mixture of tetrahydrofuran and water, and 2.5 eq of 1.0 M sodium hydroxide aqueous solution was added. The mixture was stirred at room temperature for 2 h to hydrolyze the phosphoryl chloride bond. The tetrahydrofuran was removed by concentration under reduced pressure. The residual aqueous phase was acidified to pH 2.5 with dilute hydrochloric acid, extracted three times with ethyl acetate, and precipitated with sodium chloride solid. The emulsion was broken by centrifugation, and the combined organic phases were dried over anhydrous sodium sulfate. After concentration under reduced pressure, the mixture was dissolved in dichloromethane and cooled to 0°C. A 1:1 mixture of trifluoroacetic acid and dichloromethane was added to remove the tert-butyloxycarbonyl group protection. The reaction was carried out at room temperature for 60 h. The trifluoroacetic acid was removed by concentration under reduced pressure below 40°C. A 1:1 mixture of anhydrous ethanol and dichloromethane was added to dissolve the residue. The solution was then concentrated twice under reduced pressure below 40°C to completely remove residual trifluoroacetic acid. The residue was dissolved in a 9:1 mixture of dry tetrahydrofuran and dimethylformamide. 5.5 eq of triethylamine was added, and the mixture was sonicated at 30°C for 60 min under nitrogen protection to completely dissociate and dissolve the amine salt. The solution was cooled to 0°C, and 1.05 eq of isocyanate methacrylate was added dropwise. The mixture was stirred at 0°C for 1 h, then heated to room temperature and stirred for 2 h. 0.5 eq of methanol was added, and the mixture was stirred at room temperature for 15 min to quench residual isocyanate. The residue was concentrated under reduced pressure below 40°C to remove residual methanol. The residue was dissolved in dichloromethane and treated with 0.1... The product was washed twice with dilute hydrochloric acid to remove triethylamine, then washed twice with deionized water, followed by washing with saturated sodium chloride to demulsify and remove residual water and inorganic salts. The organic phase was dried with anhydrous sodium sulfate, concentrated under reduced pressure below 40°C, and purified by neutral alumina column chromatography. The eluent was a mixture of dichloromethane and methanol in a volume ratio of 9:1, containing 0.5% to 1% triethylamine. After the reaction was complete, 0.1 wt% hydroquinone monomethyl ether was added to the feed solution as a polymerization inhibitor and maintained throughout the reaction. 0.5% hydroquinone monomethyl ether was added to the purified product.Using 1 wt% hydroquinone monomethyl ether as a polymerization inhibitor, and storing at -20°C in the dark, 2-((2-(methacryloyloxy)ethyl)ureo)-3-phenylpropyl dodecyl phosphate was obtained, with the structure shown below: .

[0044] Urea phosphate methacrylate monomer 2: prepared in-house. The preparation method is the same as that of urea phosphate methacrylate monomer 1, except that dodecyl alcohol is replaced with benzyl alcohol, while other conditions remain unchanged, to obtain urea phosphate methacrylate monomer 2.

[0045] Trisiloxane methacrylate monomer 1: Self-made, preparation method as follows: In a nitrogen-atmospheric glove box, 1.0 eq of allyl methacrylate, 0.0015 eq of 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxo radical, and platinum catalyst (approximately 4.5 ppm platinum atoms) were added to a reaction flask. The mixture was heated to 50°C under reflux condensation and nitrogen protection. Then, 1.05 eq of methyldichlorosilane was slowly added dropwise through a dropping funnel. When half the amount had been added, approximately 1.8 ppm platinum catalyst was added. After removing the heating device, the reaction was continued for 1 h using the exothermic reaction to obtain a hydrosilylated intermediate. 1.0 eq of the above hydrosilylated intermediate was dissolved in diethyl ether, and 2.2 eq of pyridine was added. The mixture was pre-cooled at 0°C for 30 min, followed by the slow dropwise addition of 2.0 eq of anhydrous toluene suspension of sodium trimethylsilanolate over 15 min. The mixture was stirred at 0°C for 1 h. After h, the precipitate was removed by filtration. The filtrate was concentrated under reduced pressure below 40℃ to remove the solvent and residual volatile impurities, yielding trisiloxane methacrylate monomer 1, with the structure shown below: .

[0046] 1 sulfonyl fluorostyrene monomer 4-Vinylbenzylsulfonyl fluoride: Prepared in-house, the preparation method is as follows: Starting with 4-chloromethylstyrene, the first step involved a nucleophilic substitution reaction between 4-chloromethylstyrene and 1.2 eq of anhydrous sodium sulfite in a mixed solvent of ethanol and water at a volume ratio of 4:1. 0.1 wt% hydroquinone monomethyl ether was added as a polymerization inhibitor. The reaction was carried out under nitrogen protection at 70°C for 10 h under reflux. After the reaction, the mixture was cooled to room temperature, filtered to remove sodium chloride precipitate, and the filtrate was concentrated to dryness under reduced pressure. The filtrate was recrystallized from anhydrous ethanol and dried under vacuum to obtain sodium 4-vinylbenzylsulfonate. The sodium 4-vinylbenzylsulfonate was then dried under vacuum at 80°C for 4 h to remove water, and then mixed with 1.1 eq of phosphorus pentachloride in dry toluene. 0.05 wt% hydroquinone monomethyl ether was added as a polymerization inhibitor, and the reaction temperature was strictly controlled to not exceed 50°C. The mixture was stirred for 4 hours. h; After the reaction was completed, the mixture was cooled to room temperature and quenched slowly in ice water with vigorous stirring. After separation, the organic phase was dried with anhydrous sodium sulfate, concentrated under reduced pressure below 40°C, and purified by silica gel column chromatography with a 6:1 volume ratio of petroleum ether to ethyl acetate as the eluent to obtain 4-vinylbenzylsulfonyl chloride; the above 4-vinylbenzylsulfonyl chloride was mixed with 2.0 eq of anhydrous potassium fluoride in dry acetonitrile, 0.05 eq of 18-crown ether-6 was added as a phase transfer catalyst, and 0.05 wt% hydroquinone monomethyl ether was added as a polymerization inhibitor. The mixture was refluxed for 12 h under nitrogen protection. The endpoint was monitored by thin-layer chromatography during the reaction. After the reaction was completed, the mixture was cooled to room temperature, filtered to remove potassium chloride precipitate, and the filtrate was concentrated under reduced pressure and purified by column chromatography with a 5:1 volume ratio of petroleum ether to ethyl acetate as the eluent to obtain 4-vinylbenzylsulfonyl fluoride, the structure of which is shown in the following formula: .

[0047] Sulfonyl fluorostyrene monomer 2: prepared in-house. The preparation method is the same as that of sulfonyl fluorostyrene monomer 1, except that 4-chloromethylstyrene is replaced with 1-(chloromethyl)-3-vinylbenzene, while other conditions remain unchanged, to obtain sulfonyl fluorostyrene monomer 2.

[0048] Preparation Examples 1-8 Preparation Example 1 Low-viscosity, high-strength silica surface treatment multi-anchoring hybrid copolymer 1: self-made, preparation method as follows: In a dry four-necked flask equipped with a mechanical stirrer, nitrogen inlet tube, reflux condenser, and constant-pressure dropping funnel, a mixed solvent of dry butanone and dry toluene in a volume ratio of 1:1 was added, with the total solid content controlled at 30 wt%. Nitrogen gas was purged for 30 min. 43 parts by weight of ureophosphate methacrylate monomer, 17 parts by weight of trisiloxane methacrylate monomer, 5 parts by weight of sulfonyl fluoride styrene monomer, 6 parts by weight of vinyltrimethoxysilane, 11 parts by weight of methyl methacrylate, 5 parts by weight of butyl acrylate, 11 parts by weight of isobornyl methacrylate, and 2 parts by weight of dimethacrylate were dissolved in the mixed solvent. One part by weight of azobisisobutyronitrile (AIBN) was added as an initiator. The reaction was carried out under a nitrogen atmosphere, heated to 75°C, and allowed to proceed for 8 h. After the reaction, the reaction solution was cooled to room temperature and slowly poured into 10 times its volume of n-hexane to precipitate the mixture. The mixture was allowed to stand for 2 hours. h, the supernatant was poured off, the precipitate was dissolved in a small amount of butanone and then poured into n-hexane to precipitate again. This process was repeated 3 times. The precipitate was then dried under vacuum to constant weight to obtain a low-viscosity, high-strength silica surface treatment multi-anchoring hybrid functional copolymer 1.

[0049] Preparation Example 2 Low-viscosity, high-strength silica surface treatment multi-anchoring hybrid functional copolymer 2: self-made, the preparation method is the same as that of low-viscosity, high-strength silica surface treatment multi-anchoring hybrid functional copolymer 1, the difference is that urea-phosphate methacrylate monomer 1 is replaced with 35 parts, trisiloxane methacrylate monomer 1 is replaced with 12 parts, sulfonyl fluorostyrene monomer 1 is replaced with 3 parts, vinyltrimethoxysilane is replaced with 4 parts, methyl methacrylate is replaced with 9 parts, butyl acrylate is replaced with 3 parts, isobornyl methacrylate is replaced with 8 parts, and ethylene glycol dimethacrylate is replaced with 1 part, all other conditions remain unchanged, to obtain low-viscosity, high-strength silica surface treatment multi-anchoring hybrid functional copolymer 2.

[0050] Preparation Example 3 Multi-anchoring hybrid functional copolymer 3 for low-viscosity high-strength silica surface treatment: self-made. The preparation method is the same as that for multi-anchoring hybrid functional copolymer 1 for low-viscosity high-strength silica surface treatment. The difference is that urea-phosphate methacrylate monomer 1 is replaced with 38 parts, trisiloxane methacrylate monomer 1 is replaced with 17 parts, sulfonyl fluorostyrene monomer 1 is replaced with 6 parts, vinyltrimethoxysilane is replaced with 8 parts, methyl methacrylate is replaced with 12 parts, butyl acrylate is replaced with 6 parts, isobornyl methacrylate is replaced with 12 parts, and ethylene glycol dimethacrylate is replaced with 1 part. All other conditions remain unchanged to obtain multi-anchoring hybrid functional copolymer 3 for low-viscosity high-strength silica surface treatment.

[0051] Preparation Example 4 Low-viscosity high-strength silica surface treatment multi-anchoring hybrid functional copolymer 4: self-made, the preparation method is the same as that of low-viscosity high-strength silica surface treatment multi-anchoring hybrid functional copolymer 1, the difference is that urea-phosphate methacrylate monomer 1 is replaced with urea-phosphate methacrylate monomer 2, and other conditions remain unchanged, to obtain low-viscosity high-strength silica surface treatment multi-anchoring hybrid functional copolymer 4.

[0052] Preparation Example 5 Low-viscosity high-strength silica surface treatment multi-anchoring hybrid functional copolymer 5: self-made, the preparation method is the same as that of low-viscosity high-strength silica surface treatment multi-anchoring hybrid functional copolymer 1, the difference is that sulfonyl fluorostyrene monomer 1 is replaced with sulfonyl fluorostyrene monomer 2, and other conditions remain unchanged, to obtain low-viscosity high-strength silica surface treatment multi-anchoring hybrid functional copolymer 5.

[0053] Preparation Example 6 Functional copolymer 6 for low-viscosity high-strength silica surface treatment: self-made. The preparation method is the same as that for low-viscosity high-strength silica surface treatment multi-anchoring hybrid functional copolymer 1, except that urea phosphate methacrylate monomer 1 is replaced with methyl methacrylate, while other conditions remain unchanged, thus obtaining functional copolymer 6 for low-viscosity high-strength silica surface treatment.

[0054] Preparation Example 7 Functional copolymer 7 for low-viscosity high-strength silica surface treatment: self-made. The preparation method is the same as that for low-viscosity high-strength silica surface treatment multi-anchoring hybrid functional copolymer 1, except that the trisiloxane methacrylate monomer 1 is replaced with methyl methacrylate, while other conditions remain unchanged, thus obtaining functional copolymer 7 for low-viscosity high-strength silica surface treatment.

[0055] Preparation Example 8 Functional copolymer 8 for low-viscosity high-strength silica surface treatment: self-made. The preparation method is the same as that for low-viscosity high-strength silica surface treatment multi-anchoring hybrid functional copolymer 1, except that the sulfonyl fluorostyrene monomer 1 is replaced with methyl methacrylate, while other conditions remain unchanged, thus obtaining functional copolymer 8 for low-viscosity high-strength silica surface treatment.

[0056] Examples 1-7 and Comparative Examples 1-4 Example 1

[0057] Low-viscosity, high-strength spherical silica 1: Self-made, preparation method as follows: Four parts of low-viscosity, high-strength silica surface treatment multi-anchoring hybrid functional copolymer 1 were dissolved in anhydrous ethanol to prepare a 5 wt% solution. 100 parts of spherical silica powder were added, wherein the mass of low-viscosity, high-strength silica surface treatment multi-anchoring hybrid functional copolymer 1 was 4% of the mass of SiO2. The mixture was ultrasonically dispersed for 30 min, and then a 1:1 volume ratio of dilute acetic acid and deionized water was added dropwise to adjust the pH of the system to 6.5. The mixture was stirred at room temperature for 8 h. After the reaction was completed, a small amount of slurry was centrifuged, dried under vacuum at 40 °C, and the Si–O–CH3 characteristic peak of the trimethoxysilane group in the copolymer was significantly weakened by Fourier transform infrared spectroscopy, confirming that the silane hydrolysis and condensation were complete. The mixture was filtered, the filter cake was washed three times with anhydrous ethanol, and dried under vacuum at 40 °C for 12 h to obtain low-viscosity, high-strength spherical silica 1.

[0058] Example 2

[0059] Low-viscosity high-strength spherical silica 2: self-made. The preparation method is the same as that of low-viscosity high-strength spherical silica 1. The difference is that the surface treatment of low-viscosity high-strength silica uses a multi-anchoring hybrid functional copolymer 1 instead of 3 parts, while other conditions remain unchanged, to obtain low-viscosity high-strength spherical silica 2.

[0060] Example 3

[0061] Low-viscosity high-strength spherical silica 3: self-made. The preparation method is the same as that of low-viscosity high-strength spherical silica 1. The difference is that the surface treatment of low-viscosity high-strength silica uses a multi-anchoring hybrid functional copolymer 1, which is replaced with 5 parts. All other conditions remain unchanged to obtain low-viscosity high-strength spherical silica 3.

[0062] Example 4

[0063] Low-viscosity high-strength spherical silica 4: self-made. The preparation method is the same as that of low-viscosity high-strength spherical silica 1. The difference is that the multi-anchoring hybrid functional copolymer 1 used for surface treatment of low-viscosity high-strength silica is replaced with multi-anchoring hybrid functional copolymer 2 used for surface treatment of low-viscosity high-strength silica. All other conditions remain unchanged to obtain low-viscosity high-strength spherical silica 4.

[0064] Example 5

[0065] Low-viscosity high-strength spherical silica 5: self-made. The preparation method is the same as that of low-viscosity high-strength spherical silica 1. The difference is that the multi-anchoring hybrid functional copolymer 1 used for surface treatment of low-viscosity high-strength silica is replaced with multi-anchoring hybrid functional copolymer 3 used for surface treatment of low-viscosity high-strength silica. All other conditions remain unchanged to obtain low-viscosity high-strength spherical silica 5.

[0066] Example 6

[0067] Low-viscosity high-strength spherical silica 6: self-made. The preparation method is the same as that of low-viscosity high-strength spherical silica 1. The difference is that the multi-anchoring hybrid functional copolymer 1 used for surface treatment of low-viscosity high-strength silica is replaced with multi-anchoring hybrid functional copolymer 4 used for surface treatment of low-viscosity high-strength silica. All other conditions remain unchanged to obtain low-viscosity high-strength spherical silica 6.

[0068] Example 7

[0069] Low-viscosity high-strength spherical silica 7: self-made. The preparation method is the same as that of low-viscosity high-strength spherical silica 1. The difference is that the multi-anchoring hybrid functional copolymer 1 used for surface treatment of low-viscosity high-strength silica is replaced with multi-anchoring hybrid functional copolymer 5 used for surface treatment of low-viscosity high-strength silica. All other conditions remain unchanged to obtain low-viscosity high-strength spherical silica 7.

[0070] Comparative Example 1 Low-viscosity high-strength spherical silica 8: self-made. The preparation method is the same as that of low-viscosity high-strength spherical silica 1. The difference is that the multi-anchoring hybrid functional copolymer 1 used for surface treatment of low-viscosity high-strength silica is replaced with the multi-anchoring hybrid functional copolymer 6 used for surface treatment of low-viscosity high-strength silica. All other conditions remain unchanged to obtain low-viscosity high-strength spherical silica 8.

[0071] Comparative Example 2 Low-viscosity high-strength spherical silica 9: self-made. The preparation method is the same as that of low-viscosity high-strength spherical silica 1. The difference is that the multi-anchoring hybrid functional copolymer 1 used for surface treatment of low-viscosity high-strength silica is replaced with functional copolymer 7 used for surface treatment of low-viscosity high-strength silica. All other conditions remain unchanged to obtain low-viscosity high-strength spherical silica 9.

[0072] Comparative Example 3 Low-viscosity high-strength spherical silica 10: self-made. The preparation method is the same as that of low-viscosity high-strength spherical silica 1, except that the multi-anchoring hybrid functional copolymer 1 used for surface treatment of low-viscosity high-strength silica is replaced with functional copolymer 8 used for surface treatment of low-viscosity high-strength silica, while other conditions remain unchanged, thus obtaining low-viscosity high-strength spherical silica 10.

[0073] Comparative Example 4 Low-viscosity high-strength spherical silica 11: self-made. The preparation method is the same as that of low-viscosity high-strength spherical silica 1. The difference is that the surface treatment of low-viscosity high-strength silica uses a multi-anchoring hybrid functional copolymer 1 instead of vinyltrimethoxysilane. All other conditions remain unchanged to obtain low-viscosity high-strength spherical silica 11.

[0074] Application Examples 1-7 and Comparative Application Examples 1-4 Application Example 1 3D printing photosensitive resin 1: S1. Mix 45 parts of acrylate resin matrix, 8 parts of reactive diluent, 1.2 parts of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 0.4 parts of isopropylthioxanthone, 0.4 parts of ethyl dimethylaminobenzoate, and 0.01 parts of hydroquinone monomethyl ether under light-protected conditions, and stir at 40°C for 30 min until completely dissolved to obtain a resin premix. S2. Add 40 parts of low-viscosity, high-strength spherical silica to the resin premix in three portions, and disperse at 2000 rpm for 30 min using a planetary high-speed disperser. S3. Vacuum degassing for 30 min yields a uniform photosensitive resin slurry; S4. Test the slurry at 25℃ and a shear rate of 10 s. -1 Record the rotational viscosity at the specified point. S5. Printed using a 405 nm wavelength DLP 3D printer, with a single-layer exposure time of 2 s and a layer thickness of 100 μm; S6. After printing, the resin is first irradiated with a 405 nm light source for 10 min for post-curing, and then heat-treated in a 60℃ oven for 30 min to obtain 3D printing photosensitive resin 1.

[0075] Application Example 2 3D printing photosensitive resin 2: self-made. The preparation method is the same as that of 3D printing photosensitive resin 1, except that the low viscosity high strength spherical silica 1 is replaced with low viscosity high strength spherical silica 2, and all other conditions remain unchanged, thus obtaining 3D printing photosensitive resin 2.

[0076] Application Example 3 3D printing photosensitive resin 3: self-made. The preparation method is the same as that of 3D printing photosensitive resin 1, except that the low viscosity high strength spherical silica 1 is replaced with low viscosity high strength spherical silica 3, and all other conditions remain unchanged, thus obtaining 3D printing photosensitive resin 3.

[0077] Application Example 4 3D printing photosensitive resin 4: self-made. The preparation method is the same as that of 3D printing photosensitive resin 1, except that the low viscosity high strength spherical silica 1 is replaced with low viscosity high strength spherical silica 4, and all other conditions remain unchanged, thus obtaining 3D printing photosensitive resin 4.

[0078] Application Example 5 3D printing photosensitive resin 5: self-made. The preparation method is the same as that of 3D printing photosensitive resin 1, except that the low viscosity high strength spherical silica 1 is replaced with low viscosity high strength spherical silica 5, and all other conditions remain unchanged, thus obtaining 3D printing photosensitive resin 5.

[0079] Application Example 6 3D printing photosensitive resin 6: self-made. The preparation method is the same as that of 3D printing photosensitive resin 1, except that the low viscosity high strength spherical silica 1 is replaced with low viscosity high strength spherical silica 6, while other conditions remain unchanged, thus obtaining 3D printing photosensitive resin 6.

[0080] Application Example 7 3D printing photosensitive resin 7: self-made. The preparation method is the same as that of 3D printing photosensitive resin 1, except that the low viscosity high strength spherical silica 1 is replaced with low viscosity high strength spherical silica 7, and all other conditions remain unchanged, thus obtaining 3D printing photosensitive resin 7.

[0081] Comparative Application Example 1 3D printing photosensitive resin 8: self-made. The preparation method is the same as that of 3D printing photosensitive resin 1, except that the low viscosity high strength spherical silica 1 is replaced with low viscosity high strength spherical silica 8, while other conditions remain unchanged, thus obtaining 3D printing photosensitive resin 8.

[0082] Comparative Application Example 2 3D printing photosensitive resin 9: self-made. The preparation method is the same as that of 3D printing photosensitive resin 1, except that the low viscosity high strength spherical silica 1 is replaced with low viscosity high strength spherical silica 9, while other conditions remain unchanged, thus obtaining 3D printing photosensitive resin 9.

[0083] Comparative Application Example 3 3D printing photosensitive resin 10: self-made. The preparation method is the same as that of 3D printing photosensitive resin 1, except that the low viscosity high strength spherical silica 1 is replaced with low viscosity high strength spherical silica 10, and all other conditions remain unchanged, thus obtaining 3D printing photosensitive resin 10.

[0084] Comparative Application Example 4 3D printing photosensitive resin 11: self-made. The preparation method is the same as that of 3D printing photosensitive resin 1, except that the low viscosity high strength spherical silica 1 is replaced with low viscosity high strength spherical silica 11, while other conditions remain unchanged, thus obtaining 3D printing photosensitive resin 11.

[0085] The following are the test methods for performance parameters involved in this invention: 1. Nuclear magnetic resonance hydrogen spectrum test: Characterization was performed using a nuclear magnetic resonance spectrometer (Bruker Avance III HD 600, 600MHz).

[0086] 2. Contact Angle Measurement: The static water contact angle of the spherical silica powder in the examples and comparative examples was determined using the seated drop method. The powder was pressed into a disc with a diameter of 13 mm and a thickness of approximately 1 mm. The contact angle of deionized water on the sample surface was measured using a contact angle meter at room temperature. The droplet volume was 2 μL, and each sample was measured 5 times at different locations. The average value was taken as the final result, and the unit is degrees. The results are shown in Table 1.

[0087] 3. Thermogravimetric Analysis (TGA): Thermogravimetric analysis was performed on the spherical silica samples of the examples and comparative examples before and after surface treatment using a thermogravimetric analyzer. The test conditions were: nitrogen atmosphere, flow rate 50 mL / min, heating rate 10℃ / min, and temperature range from room temperature to 800℃. The mass change curve with temperature was recorded, and the percentage of mass loss of the organic coating layer was calculated. The coating rate was calculated using the following formula: Coating rate (%) = [(TGA weight loss - blank weight loss) × 100%] / [(100 - TGA weight loss) × m], where m is the mass fraction of the surface treatment agent added, and the blank weight loss is 1.22%, representing the TGA weight loss rate of untreated spherical silica under the same test conditions. Using 100 parts of spherical silica as a baseline, the coating amount of the surface treatment agent on the silica surface was evaluated. The results are shown in Table 1.

[0088] 4. Rotational Viscosity Measurement: Following the specifications in GB / T 2794-2022 "Determination of Viscosity of Adhesives", a rotational viscometer was used at 25℃ and a shear rate of 10 s⁻¹. -1 The rotational viscosity of the photosensitive resin slurry in the application examples and comparative application examples was determined under the specified conditions. Before testing, the samples were placed in a constant temperature environment and allowed to stand for at least 2 hours. A suitable rotor and rotation speed were selected so that the reading was between 20% and 90% of the scale range. Each sample was tested in parallel three times, and the average value was taken as the final result. The unit is Pa·s. The results are shown in Table 2.

[0089] 5. Bending Performance Determination: Three-point bending tests were conducted according to the corresponding examples and comparative application examples specified in GB / T 9341-2008 "Determination of Bending Properties of Plastics". The specimen size was 80 mm × 10 mm × 4 mm, with a span-to-thickness ratio of 16:1. The test speed was 2 mm / min, and the ambient temperature was 23±2℃. Load-displacement curves were recorded using a universal testing machine, and the bending strength and bending modulus were calculated in MPa and GPa, respectively. Each test group consisted of no fewer than 5 specimens, and the results are shown in Table 2.

[0090] 6. Tensile property determination: Tensile tests were conducted according to the corresponding cases and comparative application examples specified in GB / T 1040.2-2022 "Determination of tensile properties of plastics - Part 2: Test conditions for molded and extruded plastics". Type 1B dumbbell-shaped specimens with a thickness of 4 mm were used. The tensile speed was 5 mm / min, and the ambient temperature was 23±2℃. Stress-strain curves were recorded, and tensile strength and elongation at break were obtained, in MPa and %, respectively. The results are shown in Table 2.

[0091] 7. Storage stability test: The photosensitive resin slurry was sealed and placed in a light-proof environment at 25℃. Samples were taken at 1, 7, 14, 30, 60 and 90 days to observe the appearance and test the rotational viscosity. The pass standard was a viscosity change rate of <10% and no visible layering. The results are shown in Table 2.

[0092] Table 1 Performance test results of the examples and comparative examples

[0093] Table 2 Performance test results of application examples and comparative application examples

[0094] As can be seen from the experimental data in Table 1, the sample examples treated with the multi-anchored hybrid functional copolymer all showed higher water contact angles than the comparative samples. Example 3, due to the use of a higher amount of copolymer treatment agent, achieved the highest contact angle and coating rate. Thermogravimetric analysis further confirmed the effective coating of the multi-anchored copolymer on the silica surface; the thermal weight loss rates of the example series were significantly higher than those of the comparative series. Comparative Example 1, lacking the urea-phosphate anchoring group, showed a decrease in both coating rate and contact angle. Although Comparative Example 2 had a higher coating rate, the replacement of trisiloxane with methyl methacrylate reduced the proportion of hydrophobic segments in the coating layer, resulting in a lack of long-chain hydrophobic shielding effect, leading to higher surface free energy and a lower water contact angle. Comparative Example 3 lacked the sulfonyl fluorostyrene polar anchoring group, weakening the dipole-dipole interactions and secondary hydrogen bonding between the copolymer and the silica surface and resin matrix, reducing interfacial polar bonding strength, and resulting in insufficient coating layer stability. Comparative Example 4, treated with a traditional single silane coupling agent, showed the lowest levels of all surface property indicators.

[0095] It is worth noting that the surface treatment in Example 1 under weakly acidic conditions (pH 6.5) resulted in a higher contact angle than that in Comparative Example 3. This result indicates that the sulfonyl fluoride group remains stable under weakly acidic conditions and is not hydrolyzed. Its strong dipole-dipole interaction and hydrophobic contribution jointly promote the realization of the high contact angle, which is completely consistent with the mechanism description in the present invention.

[0096] As can be seen from the performance data of the application examples and comparative application examples in Table 2, the slurries containing the modified silica of the example series all maintained a low level in terms of rotational viscosity, while the viscosity of the slurries of the comparative series was significantly higher. The photosensitive resins cured with the modified silica of the example series showed superior mechanical properties compared to the comparative series in terms of flexural strength, flexural modulus, tensile strength, and elongation at break. Example 5, due to the use of a copolymer treatment agent with a higher amount of functional monomers, exhibited the most outstanding performance in flexural strength, flexural modulus, and tensile strength, while having a relatively low elongation at break, reflecting the high crosslinking density and high rigidity of the interface reinforcement effect. Example 2, due to a relatively small amount of treatment agent, had a lower coating density, resulting in slightly lower flexural strength and tensile strength than other examples, but a relatively higher elongation at break, reflecting the increased toughness due to weakened interfacial bonding. The comparative examples lacked a certain anchoring group, resulting in insufficient interfacial bonding strength between the filler and the resin matrix, and reduced stress transfer efficiency. Consequently, the mechanical properties of the cured products all decreased to varying degrees, with the mechanical properties of Comparative Application Example 4 being the lowest.

[0097] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.

Claims

1. A low-viscosity, high-strength spherical silica, characterized in that, The product comprises spherical silica and a multi-anchoring hybrid functional copolymer coated on its surface, comprising, by weight, 100 parts of spherical silica and 3-5 parts of the multi-anchoring hybrid functional copolymer; the multi-anchoring hybrid functional copolymer is prepared by reacting the following monomers by weight: 35-50 parts of urea-phosphate methacrylate monomer, 12-22 parts of trisiloxane methacrylate monomer, 3-8 parts of sulfonyl fluorostyrene monomer, 4-10 parts of vinyltrimethoxysilane, 19-38 parts of acrylate modifier monomer, and 0.5-2 parts of dimethacrylate; the structure of the urea-phosphate methacrylate monomer is shown in Formula 1; the structure of the trisiloxane methacrylate monomer is shown in Formula 2; and the structure of the sulfonyl fluorostyrene monomer is shown in Formula 3. Formula 1, wherein R is selected from C8~C18 straight-chain, branched alkyl chain or benzyl; Equation 2; Equation 3, where R' is -CH2SO2F, and the substitution position is either anti- or meta-position.

2. The low-viscosity, high-strength spherical silica as described in claim 1, characterized in that, The number-average molecular weight of the multi-anchoring hybrid functional copolymer is 8000~15000; the particle size of the spherical silica is 1~50 μm; and the acrylate regulating monomer is selected from one or more of methyl methacrylate, butyl acrylate, and isobornyl methacrylate.

3. The low-viscosity, high-strength spherical silica as described in claim 1, characterized in that, The preparation method of the multi-anchoring hybrid functional copolymer includes the following steps: Urea phosphate methacrylate monomer, trisiloxane methacrylate monomer, sulfonyl fluorostyrene monomer, vinyltrimethoxysilane, acrylate modifier monomer and ethylene glycol dimethacrylate are dissolved in a mixed solvent, and an initiator is added to form a reaction solution. The reaction solution is heated to 70-80°C under nitrogen protection to carry out the polymerization reaction. After the reaction is completed, the reaction solution is cooled to room temperature, poured into a precipitant to precipitate, and after washing and drying, a multi-anchored hybrid functional copolymer is obtained.

4. The low-viscosity, high-strength spherical silica as described in claim 3, characterized in that, The mixed solvent is a mixture of butanone and toluene in a volume ratio of (0.5~2):1, with the total solid content controlled at 20%~30%; the initiator is azobisisobutyronitrile, and the amount used is 0.5%~2% of the total weight of the monomer.

5. The method for preparing low-viscosity, high-strength spherical silica according to any one of claims 1 to 4, characterized in that, Includes the following steps: The multi-anchoring hybrid copolymer was dissolved in anhydrous ethanol, and spherical silica was added to the solution and ultrasonically dispersed. A mixture of dilute acetic acid and deionized water at a volume ratio of 0.5~2:1 was added dropwise to adjust the pH of the system to 5.5~7.

0. The mixture was stirred at room temperature to allow the silanoxy groups in the copolymer to undergo a condensation reaction with the surface of the silica. After the reaction was completed, the mixture was filtered, washed, and vacuum dried to obtain low-viscosity, high-strength spherical silica.

6. The method for preparing low-viscosity, high-strength spherical silica as described in claim 5, characterized in that, The dilute acetic acid is a 0.1~0.5 M aqueous solution of acetic acid.

7. A 3D printing photosensitive resin, characterized in that, Based on weight, the product comprises 30-50 parts of low-viscosity high-strength spherical silica prepared by the method of preparing low-viscosity high-strength spherical silica according to any one of claims 1-4 or any one of claims 5-6, 35-55 parts of acrylate resin matrix, 5-12 parts of reactive diluent, 1.2-2.5 parts of photoinitiator system, and 0.01-0.05 parts of polymerization inhibitor.

8. The 3D printing photosensitive resin as described in claim 7, characterized in that, The acrylate resin matrix is ​​a mixture of bisphenol A ethoxylated diacrylate and trimethylolpropane triacrylate in a mass ratio of (5~8):(2~5); the reactive diluent is 1,6-hexanediol diacrylate; the photoinitiator system is composed of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, isopropylthioxanthone, and a hydrogen donor in a mass ratio of (2~4):1:(0.5~1); the hydrogen donor is selected from ethyl dimethylaminobenzoate, methyl diethanolamine, or isooctyl dimethylaminobenzoate.

9. The method for preparing the 3D printing photosensitive resin according to any one of claims 7-8, characterized in that, Includes the following steps: S1. Mix the acrylate resin matrix, reactive diluent, photoinitiator, hydrogen donor and polymerization inhibitor under light-protected conditions, heat and stir until completely dissolved to obtain resin premix; S2. Add the low-viscosity, high-strength spherical silica to the resin premix in 2 to 4 portions, and disperse it for 20 to 40 minutes at 1500 to 2500 rpm using a planetary high-speed disperser. S3. Vacuum degassing for 20~40 min to obtain a uniform photosensitive resin slurry.

10. The application of the 3D printing photosensitive resin as described in any one of claims 7-8 in photopolymerization 3D printing, characterized in that, The printing process uses a DLP-type 3D printing device with a wavelength of 405 nm. The single-layer exposure time is 1.5~3 s, and the layer thickness is 50~150 μm. After printing, the layer is first irradiated with a 405 nm light source for 5~15 min for post-curing, and then heat-treated in an oven at 55~65℃ for 20~40 min.